2020
DOI: 10.1007/s13224-020-01334-4
|View full text |Cite
|
Sign up to set email alerts
|

Three Thousand Cases of Office Hysteroscopy: See and Treat an Indian Experience

Abstract: Study Objective Assessment of feasibility of office hysteroscopy in Indian setting. Design Retrospective study design. Setting Tertiary care centre: Galaxy care Hospital,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Of these, 290 studies did not match the eligibility criteria, and 16 full‐text studies were shortlisted. Nine studies were excluded due to different study designs, different operative techniques, the use of different distention media, or different outcome measures 9,17–24 . Finally, seven randomized controlled trials 8,10,11,25–28 were included in qualitative synthesis (systematic review) and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 290 studies did not match the eligibility criteria, and 16 full‐text studies were shortlisted. Nine studies were excluded due to different study designs, different operative techniques, the use of different distention media, or different outcome measures 9,17–24 . Finally, seven randomized controlled trials 8,10,11,25–28 were included in qualitative synthesis (systematic review) and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were excluded due to different study designs, different operative techniques, the use of different distention media, or different outcome measures. 9,[17][18][19][20][21][22][23][24] Finally, seven randomized controlled trials 8,10,11,[25][26][27][28] were included in qualitative synthesis (systematic review) and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…A recent meta‐analysis by De Silva et al in 2020 6 calculated an overall success rate of 95% for vaginoscopic hysteroscopy. Three Indian studies in this regard by Misra et al, 7 Telang et al, 8 and Gupta et al 9 have reported success rates of 79%, 98.66%, and 83%, respectively. VAGI was successful in 80% of cases, which is comparable to the cited literature, but CVH was successful in only 33.3% cases.…”
Section: Discussionmentioning
confidence: 98%